1996
DOI: 10.1021/es960141u
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Mineralogical Characterizations of Pb in a Contaminated Soil:  Reactions with Synthetic Apatite

Abstract: Previous studies have shown that the interactions of apatite with dissolved Pb are caused by the dissolution of apatite grains concomitant with the precipitation of lead orthophosphates (pyromorphites). The present study extends this work by examining the interactions of selected Pb minerals and a Pbcontaminated soil with apatite. Specimen-grade PbO and PbCO 3 were reacted separately with hydroxylapatite (HA) in controlled pH reactors. Hydroxypyromorphite (HP) formed at the expense of HA, PbO, and PbCO 3 after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
0
5

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(146 citation statements)
references
References 13 publications
6
131
0
5
Order By: Relevance
“…The pH range of [2][3][4][5][6][7] was selected to simulate the pH values in the GI tract that has been diseussed elsewhere (19). Reactions were carried out under static pH condition (pH-constant) and in suspensions in which the pH was adjusted'from 2 to 7 within 30 min (pH-dynamic).…”
Section: Methodsmentioning
confidence: 99%
“…The pH range of [2][3][4][5][6][7] was selected to simulate the pH values in the GI tract that has been diseussed elsewhere (19). Reactions were carried out under static pH condition (pH-constant) and in suspensions in which the pH was adjusted'from 2 to 7 within 30 min (pH-dynamic).…”
Section: Methodsmentioning
confidence: 99%
“…The NRMRL research program's initial goal was to demonstrate the feasibility of altering the mineralogy of lead in soil in a laboratory setting by using thermodynamic and kinetic studies. Orthophosphate (aqueous phosphorus, hydroxyapatite, or phosphate rock) rapidly and effectively precipitates lead from solution to form a series of lead phosphates of low aqueous solubilities (27,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). The final product of lead immobilization is primarily pyromorphite [Pb 5 (PO 4 ) 3 X, where X is OH, Cl, or F], which is stable under normal soil environmental conditions.…”
Section: Reducing Exposurementioning
confidence: 99%
“…Further, environmentally relevant concentrations of other metals had no significant effect on lead immobilization by hydroxyapatite; in fact, hydroxyapatite may remove the metals (38). Also, pyromorphite formation from lead adsorbed on goethite (Fe(OH) 3 ) (39) and primary lead minerals, including cerrusite (PbCO 3 ) (40, 41), anglesite (PbSO 4 ) (42), litharge (PbO) (40), massicot (PbO) (40), and galena (PbS) (43), by addition of apatite have been reported. The completeness and kinetics of this transformation depend on the mineralogy of lead, the amount of apatite added, and the pH of the system.…”
Section: Reducing Exposurementioning
confidence: 99%
“…Similarly, Ma et al (1995) and Laperche et al (1997) observed a peak at 2.96 Å upon P addition to a Pb-contaminated soil. Thermodynamic considerations predict that Pb phosphate minerals are the most stable among Pb compounds (Laperche et al, 1996;Seaman et al, 2003). Thus, they can be readily formed in the presence of adequate Pb and P. Ruby et al (1994) also demonstrated that the weathering of galena (PbS) to insoluble lead phosphates occurred in soils at a port facility historically used for shipment of phosphate.…”
Section: X-ray Diffractionmentioning
confidence: 99%